Forty thieves ebook - Perry, Thomas (2015)
Married sleuths cross paths with married assassins in this “priceless” mystery by the bestselling author of the Jane Whitefield series ( The New York Times ).   Sid and Ronnie Abel are a first-rate husband-and-wife detective team, both ex-LAPD. Ed and Nicole Hoyt are married assassins-for-hire living in the San Fernando Valley. Except for deadly aim with a Glock 17, the couples have little in common—until they’re hired to do damage control on the same murder. The body of research scientist James Ballantine has been pulled from a storm sewer, with two bullet holes in the back of his head.   With the case turning cold, Ballantine’s former employers bring in the Abels to succeed where the police have failed. As for the Hoyts, their mysterious contractors want to make sure that the facts about Ballantine’s death stay hidden. Now the Abels must try to survive as they circle ever closer to the truth, and to a dangerous pair guarding it with their lives. From “a master of nail-biting suspense” ( Los Angeles Times ), comes a “propulsive, darkly humorous” ( Publishers Weekly ) “double-barreled Southern California thriller that moves almost faster than a speeding bullet” ( The Wall Street Journal ).